SPATIAL REGRESSION MODEL ANALYSIS OF TRAFFIC VOLUME AND SPEED IN KEDIRI CITY - Mochammad Danara Indra Pradigta; Evita Fitrianis Hidiyati; Andri Dwi Cahyono; Faiz Muhammad Azhari; Muhamad Kusaini; Tahta Mihrobul Muna (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
Urban development is often accompanied by traffic challenges, particularly the increasing volume of vehicles that is not commensurate with the capacity of road infrastructure. This study aims to evaluate the effect of spatial heterogeneity of vehicle volume and type on vehicle speed at four main intersections in Kediri City: Alun-Alun, Semampir, Bandar Alim, and Kawi. A quantitative approach was used through direct observation, floating car method, and linear regression analysis and ANOVA. The results show that intersections with high vehicle volume tend to have lower speeds, especially when dominated by heavy vehicles. Alun-Alun intersection has the highest R-Square value for vehicle volume (0.847), while Bandar Alim intersection recorded the highest R-Square for vehicle speed (82%). T-test and ANOVA indicate a significant effect of vehicle direction and type on speed, especially at Semampir and Bandar Alim. These findings demonstrate the importance of integrating volume and speed in traffic management, as well as the need for a data-driven and spatial approach in developing intelligent transportation systems. Therefore, it is necessary to discuss further in the objectives and body of the research regarding the causal relationship between vehicle volume, vehicle type composition, travel direction, and spatial variations between intersections, so that the research results can provide a stronger scientific basis for adaptive traffic management policies to the specific conditions of each intersection.